QTL Analysis of Spike Morphological Traits and Plant Height in Winter Wheat (Triticum aestivum L.) Using a High-Density SNP and SSR-Based Linkage Map - Zhai, Huijie; Feng, Zhiyu; Li, Jiang; Liu, Xinye; Xiao, Shihe; Ni, Zhongfu; Sun, Qixin (Frontiers in Plant Science, 2016)
Wheat yield can be enhanced by modifying the spike morphology and the plant height. In this study, a population of 191 F9 recombinant inbred lines (RILs) was developed from a cross between two winter cultivars Yumai 8679 and Jing 411. A dense genetic linkage map with 10,816 markers was constructed by incorporating single nucleotide polymorphism (SNP) and simple sequence repeat (SSR) marker information. Five spike morphological traits and plant height were evaluated under nine environments for the RILs and parental lines, and the number of detected environmentally stable QTLs were 18 and 3, respectively. The 1RS/1BL (rye) translocation increased both spike length and spikelet number with constant spikelet compactness. The QPht.cau-2D.1 was identical to gene Rht8, which decreased spike length without modifying spikelet number. Notably, four novel QTLs locating on chromosomes 1AS (QSc.cau-1A.1), 2DS (QSc.cau-2D.1) and 7BS (QSl.cau-7B.1 and QSl.cau-7B.2) were firstly identified in this study, which provide further insights into the genetic factors that shaped the spike morphology in wheat. Moreover, SNP markers tightly linked to previously reported QTLs will eventually facilitate future studies including their positional cloning or marker-assisted selection.